Toward the future of the halal industry: exploring perceptions and halal awareness among poultry slaughterhouse business practitioners - Hikmah, Lailatul; Pertiwi, Tanza Dona; Cholil, Muhammad; Susanto, Arva Athallah; Soleh, Mochammad; Widiastuti, Tika (Journal of Halal Product and Research (JHPR), 2025)
The halal industry has become an integral part of the global economic structure, especially in countries with a majority Muslim population. In Indonesia, significant potential is evident, particularly in the halal food business, both domestically and internationally. However, to foster it, a sustainable halal supply chain requires confirmation or assurance of product halalness. However, this also poses challenges related to awareness and perceptions of halal among business operators, making finding solutions crucial. This research employs a qualitative approach through observation, interviews, and data collection documentation. Research findings indicate that business operators' perceptions and awareness are still limited; thus, there is no impetus to obtain halal certification. Moreover, the results show that business operators face barriers related to halal certification, particularly concerning costs and insufficient socialisation received, leading to a lack of awareness of the necessity of halal certification. However, for already certified halal business operators, such accreditation is considered a good product brand image, supports business sustainability, and opens up new opportunities. Practitioners and academics also concur, identifying costs and socialisation as field constraints. This research focuses on overcoming cost and administrative difficulties, reviewing legislation, and implementing socialization efforts that should reach all business operators. The government and halal centers expect this research to serve as a reference to achieve the future goals of the halal industry in Indonesia. Keywords: Halal Industry, Perceptions, Halal Awareness, Cutting Household Entrepreneurs, Halal Certified